2011
DOI: 10.1007/978-3-642-22006-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Pairwise-Interaction Games

Abstract: Abstract. We study the complexity of computing Nash equilibria in games where players arranged as the vertices of a graph play a symmetric 2-player game against their neighbours. We call this a pairwiseinteraction game. We analyse this game for n players with a fixed number of actions and show that (1) a mixed Nash equilibrium can be computed in constant time for any game, (2) a pure Nash equilibrium can be computed through Nash dynamics in polynomial time for games with a symmetrisable payoff matrix, (3) dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Finally, potential games on graphs (every node plays some potential game with each neighbor) characterize the class of potential games for which the equilibria of noisy best-response dynamics with all players updating simultaneously can be "easily" computed [3]. The convergence time of best-response dynamics for games on graphs is studied in [12,17]: Among other results, [12] showed that a polynomial number of steps are sufficient when the same game is played on all edges and the number of strategies is constant. Analogous results are proven for finite opinion games in [17].…”
Section: Related Workmentioning
confidence: 99%
“…Finally, potential games on graphs (every node plays some potential game with each neighbor) characterize the class of potential games for which the equilibria of noisy best-response dynamics with all players updating simultaneously can be "easily" computed [3]. The convergence time of best-response dynamics for games on graphs is studied in [12,17]: Among other results, [12] showed that a polynomial number of steps are sufficient when the same game is played on all edges and the number of strategies is constant. Analogous results are proven for finite opinion games in [17].…”
Section: Related Workmentioning
confidence: 99%
“…Recently, much attention has been devoted to games played on social networks. In particular, Dyer and Mohanaraj [17] introduced a class of graphical games, called pairwise-interaction games, in which players are placed on vertices of a graph and there is a unique game being played on the edges of this graph. They prove, among other results, quick convergence of best-response dynamics for these games.…”
Section: Related Workmentioning
confidence: 99%
“…To address this issue we will not apply the technique on the original game but on an "equivalent" game. Specifically, we use the following definition, previously used in [17].…”
Section: Best-response Dynamicsmentioning
confidence: 99%
“…Another related work is [14] by Dyer and Mohanaraj. They study graphical games, called pairwise-interaction games, and prove among other results, quick convergence of best-response dynamics for these games.…”
Section: Related Workmentioning
confidence: 99%